Butyricimonas phoceensis sp. nov., a new anaerobic species isolated from the human gut microbiota of a French morbidly obese patient. (November 2016) - Togo, A.H.; Diop, A.; Dubourg, G.; Nguyen, T.T.; Andrieu, C.; Caputo, A.; Couderc, C.; Fournier, P.-E.; Maraninchi, M.; Valero, R.; Raoult, D.; Million, M.
Abstract: Butyricimonas phoceensis strain AT9 (= CSUR 2478 = DSM 100838) was isolated from a stool sample from a morbidly obese French patient living in Marseille using the culturomics approach. The genome of this Gram-negative-staining, anaerobic and non–spore forming rod bacillus is 4 736 949 bp long and contains 3947 protein-coding genes. Genomic analysis identified 173 genes as ORFans (4.5%) and 1650 orthologous proteins (42%) not shared with the closest phylogenetic species, Butyricimonas virosa . Its major fatty acid was the branched acid iso-C15:0 (62.3%).